Literary Texts Utilization in Distant Teaching of Russian Language - Zoya Şengüder (Avrasya İncelemeleri Dergisi)
In our study, the application of distance learning principles is discussed through the example of an online class that used a literary text developed for Istanbul University Faculty of Literature, Russian Language and Literature Department students. In this study, Russian contemporary author Yu. Ya. Yakovlev’s, “Skripka” (“Tne violin”) story was used in the second class (B1 level) of an Oral and Written Composition online lesson. The aim of this study is the development of an algorithm that both meets the needs and boosts the motivation of foreign students learning Russian as a foreign language by using literary texts, and by presenting conclusions or principles of online classes. The topicality level of this study is determined by the need to understand new educational conditions, improve the process of teaching Russian as a foreign language as well as to improve the quality of education and motivation of foreign students learning Russian remotely.